Reusable concrete debris as aggregate replacement on the properties of green concrete - Md Husain, Nadiah; Razak, A.A.A.; Wan Azahar, Wan Nur Aifa; Kasim, Norhidayu; Ismail, Norfarah Nadia; Saad, Siti Asmahani; Masjuki, Siti Aliyyah; Ibrahim, Saerahany Legori; Ramli, Ahmad Bukhari (Springer International Publishing, 2020)
The sustainability of renewable resources is affected by the rapid booming of the construction sector. The massive production of construction and demolition waste by this sector has given drawbacks to the environment as well. An environmentally friendly approach to overcome the disposal of waste materials is via the recycling process. The main objective of this study is to investigate the properties of concrete made by Coarse Aggregate Associated with Concrete Production (CAACP) and Fine Aggregate Associated with Concrete Production (FAACP). Both CAACP and FAACP were obtained from concrete debris from crushed concrete. Some percentage of the concrete debris will be used as an aggregate replacement for concrete production. Six different concrete mixes containing 10, 20 and 30% of coarse and fine aggregate replacement were prepared accordingly. The concrete samples were tested for its strength at 3,7 and 28 days of curing age. The physical properties of the recycle aggregate were also carried out in order to investigate the possible factor that may affect the fresh and hardened concrete. It can finally be concluded that green concrete can be produced by FAACP or CAACP and possibly to produce higher strength compared to the conventional concrete strength.